2016
DOI: 10.1371/journal.pone.0161883
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection of the Central Nervous System Exacerbates Interleukin-10 Receptor Deficiency-Mediated Colitis in SJL Mice

Abstract: Theiler´s murine encephalomyelitis virus (TMEV)-infection is a widely used animal model for studying demyelinating disorders, including multiple sclerosis (MS). The immunosuppressive cytokine Interleukin (IL)-10 counteracts hyperactive immune responses and critically controls immune homeostasis in infectious and autoimmune disorders. In order to investigate the effect of signaling via Interleukin-10 receptor (IL-10R) in infectious neurological diseases, TMEV-infected SJL mice were treated with IL-10R blocking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 128 publications
(161 reference statements)
1
16
0
Order By: Relevance
“…IL-10 is one of the most important anti-inflammatory cytokines as reviewed by Sabat et al . 61 and its ablation induces severe failure in immune homeostasis causing inflammatory disorders such as colitis 62 . In the context of helminth infection, parasite-induced IL-10 secretion may enhance the homeostatic capacity of the host including elevated generation of Tregs 63 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is one of the most important anti-inflammatory cytokines as reviewed by Sabat et al . 61 and its ablation induces severe failure in immune homeostasis causing inflammatory disorders such as colitis 62 . In the context of helminth infection, parasite-induced IL-10 secretion may enhance the homeostatic capacity of the host including elevated generation of Tregs 63 .…”
Section: Discussionmentioning
confidence: 99%
“…25 five-week old female SJL and 5 five-week old female C57BL/6 mice (Harlan Winkelmann) were inoculated with 1.63 × 10 6 PFU of TMEV (BeAn-strain, 0 days post infection [dpi]) into the right cerebral hemisphere following general anesthesia, as described previously 25 . In the first experiment, necropsy was performed in groups of five SJL animals at 4, 7 and 14 dpi, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies on IL-10 in TME revealed only limited effects of anti-IL-10R treatment on spinal cord lesions and virus load in SJL mice during the chronic disease 25 . In acute TME, an elevated Il10 expression primarily by infiltrating T cells was observed in the brain of SJL mice compared to those of seizure-prone C57BL/6 mice 26 .…”
Section: Introductionmentioning
confidence: 91%
“…In experiment 4, also hematoxylin + eosin (HE)-stained sections (at −1.7 to −1.82 mm from bregma) were used to measure hypercellularity in the hippocampus after kainate. The extent of hypercellularity was scored as described previously 44 : 1 = 1–25 cells, 2 = 26–50 cells, 3 = > 50 cells per high power field.…”
Section: Methodsmentioning
confidence: 99%